THE INFLUENCE OF FINANCIAL ATTITUDE, PERSONALITY, FINANCIAL TECHNOLOGY, AND LEVEL OF FINANCIAL KNOWLEDGE ON FINANCIAL MANAGEMENT OF MSMES IN SIDOARJO (STUDY ON CREATIVE CRAFT AND SERVICE MSMES) - Akhmad Zainur Roziqin Al Barizi; Sriyono Sriyono (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the influence of financial attitude, personality, financial technology, and financial knowledge level on financial management among Micro, Small, and Medium Enterprises (MSMEs) in the creative craft and service sectors in Sidoarjo, Indonesia. Method: A quantitative research design was applied using a survey method, with questionnaires distributed to 146 registered and government-supported MSMEs under the supervision of the Sidoarjo Department of Cooperatives and MSMEs. Data analysis was conducted using SmartPLS 3.0 to test the relationships among variables. Results: The study is expected to reveal that positive financial attitudes, favorable personality traits, higher levels of financial knowledge, and active use of financial technology significantly enhance the financial management capabilities of MSME actors. These factors collectively strengthen financial decision-making and operational sustainability. Novelty: This research contributes by integrating psychological, technological, and knowledge-based perspectives in explaining MSME financial behavior, offering empirical evidence that supports policy development aimed at improving financial literacy and promoting the adoption of financial technology to enhance MSME resilience and growth.